The Significance and Cultivation Technology of the Medicinal Plant Shepherd’s Purse - Latifbayeva R.U (American Journal of Botany and Bioengineering, 2025)
The flora of Uzbekistan includes more than 4,000 plant species. About 20% of these species are endemic (not found anywhere else); most of them grow in mountainous areas. Representatives of the plant Shepherd’s Purse (Capsella Bursa-Pastoris L. Medic) are widespread in nature and are distinguished by their medicinal properties. The plant has remarkable characteristics that positively affect the human body